Optimizing Business Communication Strategy to Increase Consumer Interest in Purchasing in the Digital Era - Rojikun, Ahmad; Darda, Ahmad (Universitas Mohammad Husni Thamrin, 2025)
Digital transformation has become a catalyst for major changes in the global business landscape. The development of information technology has driven a major transformation in business communication practices, particularly in efforts to influence consumer behavior in the digital era. This era is marked by fundamental changes in consumer behavior, who are now more active, critical, and constantly connected with brands through various digital platforms such as social media, e-commerce, discussion forums, and mobile applications. Communication strategies that were previously one-way must now evolve to be interactive, personalized, and data-driven. This study aims to analyze how optimizing business communication strategies can increase consumer interest in purchasing decisions, especially in the context of a dynamic and competitive digital environment. Using a descriptive qualitative approach, this study examines various elements of digital communication such as content marketing, social media, message personalization, and the use of technologies such as artificial intelligence and consumer analytics. The results of the study indicate that integrated, relevant, and responsive business communication significantly influences consumer perceptions, trust, and purchase intentions. These findings emphasize the importance of strategic communication management that not only conveys information but also builds emotional engagement and meaningful digital experiences. Thus, this study recommends that companies adopt a technology- and data-based communication approach to create more effective, adaptive, and consumer experience-oriented interactions as an effort to increase competitiveness in the digital marketplace.